Copper(I)/Bpy‐Catalyzed C‐2‐H Benzylation of Quinazolin‐4(3H)‐ones with N‐Tosylhydrazones. Issue 19 (11th May 2020) - Li, Fei; Gu, Xiao‐Juan; Zeng, Chang‐E.; Li, Xia; Liu, Bo; Huang, Guo‐Li
Abstract : A general and efficient copper‐catalyzed C–H benzylation reaction of quinazolin‐4(3 H )‐ones with N ‐tosylhydrazones is reported. The formation of new C(sp 3 )–C(sp 2 ) bonds through cross‐coupling occurs at the electron‐poor C‐2 position of quinazolin‐4(3 H )‐one and represents an exceedingly practical method to afford 2‐benzylated quinazolin‐4(3 H )‐ones in moderate to good yields under mild reaction conditions. A possible reaction mechanism for this transformation was proposed. This catalytic transformation has the potential to be an important synthetic application for the late‐stage functionalization of advanced synthetic intermediates. Abstract : Regioselective C‐2‐H benzylation of quinazolin‐4(3 H )‐ones with N ‐tosylhydrazones in a ligand dependent copper system was studied. An array of substituted quinazolin‐4(3 H )‐ones were coupled effectively with a wide variety of N ‐tosylhydrazones derived from aryl ketones to afford the alkylated products in moderate to good yields. This is a useful, time‐efficient, and scalable procedure for the construction of C(sp 2 )–C(sp 3 ) bonds.